THE INFLUENCE OF PRODUCT DIFFERENTIATION, PRODUCT INNOVATION, FACTOR OF CULTURAL, SOCIAL, PERSONAL AND PSYCHOLOGICAL ON PURCHASING DECISIONS - Paseru, Olivia Ribkah datu; Ginting, Ari Mulianta (LPPM STIE Muhammadiah Bandung, 2024)
This research aims to determine whether product differentiation, product innovation, cultural, social, personal and psychological factors influence consumers' decisions to buy something. This case study uses a sample of visitors to the Indonesian Creation Appreciation exhibition in Samarinda and Surabaya. The model used for this research was 232 respondents. They come from the target population who visited the exhibition in Samarinda and Surabaya. Next, the Partial Least Square Structural Equation Modeling (PLS-SEM) approach provided by SmartPLS 3.0 was used to process and analyze the collected questionnaire data. The data processing results show that product differentiation, product innovation, and social, personal and psychological factors have a significant and positive influence on purchasing decisions. Purchasing decisions are not influenced by culture.